2018
DOI: 10.1155/2018/4653937
|View full text |Cite
|
Sign up to set email alerts
|

Creep Strain and Permeability Evolution in Cracked Granite Subjected to Triaxial Stress and Reactive Flow

Abstract: Fluid flow and fluid-rock interaction mainly take place in fracture network, consequently resulting in deformation and permeability variation of rock and deterioration of the wellbore performance. Mechanical-reactive flow coupling creep tests are performed on cracked granite under various confining pressures and acid and alkaline solution flows. The testing results show that the confining pressure and solution pH significantly influence the creep deformation, creep strain rate, and permeability. A primary cree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The contents of mica and potassium feldspar show a downward trend during the immersion process, and the decreasing rates of mass percentage are, respectively, 43.55% and 62.96% after chemical corrosion for 90 days. This phenomenon is attributed to the reaction of mica and potassium feldspar in an acidic environment (Equations (2) and (3)) [36,37]. However, the content of quartz and sodium feldspar slightly ascends with the increase of the immersed time, and the content of chlorite appears to fluctuate.…”
Section: Geofluidsmentioning
confidence: 99%
“…The contents of mica and potassium feldspar show a downward trend during the immersion process, and the decreasing rates of mass percentage are, respectively, 43.55% and 62.96% after chemical corrosion for 90 days. This phenomenon is attributed to the reaction of mica and potassium feldspar in an acidic environment (Equations (2) and (3)) [36,37]. However, the content of quartz and sodium feldspar slightly ascends with the increase of the immersed time, and the content of chlorite appears to fluctuate.…”
Section: Geofluidsmentioning
confidence: 99%
“…There has been considerable research on rock behavior under chemical erosion environments for rock specimens. For example, Zhang et al [ 19 ] conducted creep tests on cracked granite under various confining pressures and different chemical solutions, and they found that an acid solution has a more obvious influence on the creep behavior than that of an alkaline solution. Hu et al [ 20 ] proposed constitutive models to describe the mechanical responses of cement-based material subjected to a long-term chemo-mechanical coupling effect.…”
Section: Introductionmentioning
confidence: 99%